PERKEMBANGAN PENDIDIKAN DI INDONESIA DARI ERA KEMERDEKAAN HINGGA ERA REFORMASI (1945 – 2008) - DAHLENA SARI MARBUN (JURNAL ILMIAH MAKSITEK, 2020)
Education in Indonesia must refer to two basic principles, namely the 1945 Constitution (UUD '45) and the national philosophy of Pancasila. Indonesia's main problem now is the implementation of national education that is not in accordance with the two basic principles of the nation. Education which should be based on the life line and national culture and aims to meet the needs of life to elevate the state and honor human beings, a commitment of the Indonesian nation that has been outlined by one of the founders of the nation who is also the Father of Indonesian Education Ki Hajar Dewantara, in fact, always deviates and does not in accordance with the 1945 Constitution and Pancasila. The orientation and education system in the history of Indonesia has changed from patriotism (early independence), regional autonomy (the United Republic of Indonesia), socialist-communism (Manipol-USDEK), liberal (New Order) and neo-liberal (Reformasi). This study tries to determine the factors that cause this deviation through a discussion of the orientation and education system that has been implemented in Indonesia.